2016
DOI: 10.1165/rcmb.2015-0332oc
|View full text |Cite
|
Sign up to set email alerts
|

Elevated MicroRNA-33 in Sarcoidosis and a Carbon Nanotube Model of Chronic Granulomatous Disease

Abstract: We established a murine model of multiwall carbon nanotube (MWCNT)-induced chronic granulomatous disease, which resembles human sarcoidosis pathology. At 60 days after oropharyngeal MWCNT instillation, bronchoalveolar lavage (BAL) cells from wild-type mice exhibit an M1 phenotype with elevated proinflammatory cytokines and reduced peroxisome proliferator-activated receptor γ (PPARγ)-characteristics also present in human sarcoidosis. Based upon MWCNT-associated PPARγ deficiency, we hypothesized that the PPARγ t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 31 publications
(37 reference statements)
3
27
0
Order By: Relevance
“…Our previous studies have shown deficiency of PPARγ, ABCA1 and ABCG1 in alveolar macrophages from both sarcoidosis patients and the 60 day MWCNT model [13,19,30]. The inflammatory mediators, chemokine (C-C motif) ligand-2 (CCL2) and osteopontin, were elevated in sarcoidosis granulomatous tissue and in the 60 day MWCNT model [13,34–36].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous studies have shown deficiency of PPARγ, ABCA1 and ABCG1 in alveolar macrophages from both sarcoidosis patients and the 60 day MWCNT model [13,19,30]. The inflammatory mediators, chemokine (C-C motif) ligand-2 (CCL2) and osteopontin, were elevated in sarcoidosis granulomatous tissue and in the 60 day MWCNT model [13,34–36].…”
Section: Resultsmentioning
confidence: 99%
“…Our recent studies in alveolar macrophages from sarcoidosis patients and MWCNT-instilled mice observed decreased expression of both ABCG1 and ABCA1 [30]. The deficiency of these lipid transporters correlates with increased alveolar macrophage lipid accumulation in MWCNT-instilled animals [30]. These observations suggest that downregulation of ABCG1 and ABCA1 may contribute to MWCNT-induced inflammation.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In nematode Caenorhabditis elegans (C. elegans), MWCNT differentially regulated 55 miRNAs, of which 5 miRNAs had a protective role and 7 miRNAs played a role in MWCNT toxicity . In bronchoalveolar lavage cells and lung granulomas, MWCNT increased miRNA‐33 expression …”
Section: Introductionmentioning
confidence: 99%
“…26 In bronchoalveolar lavage cells and lung granulomas, MWCNT increased miRNA-33 expression. 27 Our previous study showed that MWCNT activate alveolar epithelial A549 cells to express fibrosis markers TGFb and Col 3A1. MWCNT induced TGFb by 2.62-, and Co3A1 by 2.34-fold change versus control.…”
mentioning
confidence: 96%